Terapi Slow Stroke Back Massage terhadap Peningkatan Kualitas Tidur Pasien Chronic Kidney Disease (CKD) yang Menjalani Hemodialisis - Dewi Astuti Sudijanto; Fitri Arofiati (Jurnal Keperawatan Silampari, 2022)
quality of patients with Chronic Kidney Disease who received hemodialysis treatment. This research method uses a Quasi-Experimental Design with a Pretest – Post-test Group Design approach. The results showed that in the intervention group the p-value = 0.005 (p < 0.05), the control group the p-value = 1,000 (p > 0.05). In conclusion, the SSBM technique affects improving sleep quality in CKD patients receiving HD treatment. In the intervention group, there was a difference in the sleep quality of HD patients before and after being given SSBM, while in the control group, there was no difference. Keywords: Hemodialysis, Sleep Quality, Chronic Kidney Disease